IN SILICO DESIGN OF QUINOXALINE BEARING THIAZOLIDINONE DERIVATIVES AS PPARγ AGONIST IN DIABETES MELLITUS - T, POORNIMA; PT, MANJU; E, ANJANA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Diabetes mellitus is a set of metabolic disease in which there is increased blood sugar level over a long period. The objective of the study is in silico design of quinoxaline bearing thiazolidinone derivatives as peroxisome proliferator-activated receptor gamma (PPARγagonist in diabetes mellitus. Methods: In silico design of proposed derivatives was conducted by ACD Lab ChemSketch 12.0 and derivatives obeying Lipinski’s rule of five were selected for docking studies. Docking was carried out using AutoDock Vina software. Results: Molinspiration results revealed that the designed derivatives had physical and chemical properties meant for an orally available drug. Based on the docking results derivatives, QNT1 and QNT2 exhibited high docking score which indicates that these derivatives possess high-affinity and high polar interaction toward protein 1PRG (ligand-binding domain of human peroxisome proliferator-activated receptor gamma). Conclusion: The designed quinoxaline bearing thiazolidinone derivatives were found to possess good binding affinity and good interaction in the binding pocket of target 1PRG, so these derivatives are expected to exhibit good antidiabetic property with minimal side effects.